State of School Feeding Worldwide 2013 - World Food Programme (World Food Programme, Rome, 2013)
In 2009, the World Bank (WB) and the World Food Programme (WFP), in collaboration with the Partnership for Child Development (PCD), published an analysis called Rethinking School Feeding. The analysis was undertaken to better understand the growing demand from countries for school feeding programmes that was sparked by the food, fuel, and financial crises of 2008. This report seeks to build on the 2009 analysis and begin a systematic process to better understand the strengths and challenges of school feeding programmes globally. It presents the current status of our understanding of school feeding. Information was drawn from a global survey conducted by WFP in early 2012 and a series of case studies and peer-reviewed technical working papers undertaken in collaboration with partners. The analysis led to the identification of new areas that require more focused attention. The report highlights these areas and outlines the current research agenda on which WFP and its partners are currently collaborating.